1997
DOI: 10.1038/bjc.1997.277
|View full text |Cite
|
Sign up to set email alerts
|

The location of acidic fibroblast growth factor in the breast is dependent on the activity of proteases present in breast cancer tissue

Abstract: Summary Acidic fibroblast growth factor (FGF1) and two of its receptors, FGFR1 and FGFR4, were localized in cryostat sections of normal, benign and malignant human breast tissue by immunohistochemistry. Without pretreatment, FGF1 staining was mainly seen in normal epithelial cells. However, polymerase chain reaction (PCR) analysis and immunoblotting of isolated normal epithelial and myoepithelial cells showed FGF1 mRNA and protein to be present in both cell types. Following incubation of frozen sections at 370… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…Previous work has shown that FGF1 and FGF2 are present in large amounts in the normal breast, implying roles for these growth factors in maintaining the structure of the normal ducts (Gomm et al, 1991Coope et al, 1997). In breast cancer, there is a decrease in the amount of FGF1 and FGF2 present in breast tissue (Bansal et al, 1995;Yiangou et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that FGF1 and FGF2 are present in large amounts in the normal breast, implying roles for these growth factors in maintaining the structure of the normal ducts (Gomm et al, 1991Coope et al, 1997). In breast cancer, there is a decrease in the amount of FGF1 and FGF2 present in breast tissue (Bansal et al, 1995;Yiangou et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, there is a decrease in the amount of FGF1 and FGF2 present in breast tissue (Bansal et al, 1995;Yiangou et al, 1997a). However, in the case of FGF1, there is evidence for some remaining in a more functionally available form in breast cancers (Smith et al, 1994;Coope et al, 1997). FGF7 is found in similar amount in both malignant and non-malignant breast tissue.…”
Section: Introductionmentioning
confidence: 99%
“…All four of the FGFRs are expressed to some degree in breast cell lines (McLeskey et al, 1994;Johnston et al, 1995). Although amplification of the fgfr4 gene has been found in 10% of breast cancers, we have previously shown that equivalent levels of FGFR-4 are present in the epithelial cells of malignant and non-malignant breast sections (Jaakkola et al, 1993;Coope et al, 1997). In the case of FGFR-1, significant changes in the isoform of FGFR-1 expressed occur on malignant transformation although the level of expression appears to stay the same Yiangou et al, 1997b).…”
mentioning
confidence: 90%
“…Previous work has shown that FGF1 and FGF2 are expressed in the normal breast, implying roles for these growth factors in maintaining the structure of the normal ducts (Gomm et al, 1991Coope et al, 1997). In breast cancer, there is a decrease in the amount of FGF1 and FGF2 present in breast tissue (Bansal et al, 1995;Yiangou et al, 1997a).…”
mentioning
confidence: 99%
See 1 more Smart Citation